Taxonomy, Lectotypification, and Conservation of the Genus Phyllodium (Fabaceae: Desmodieae) in Cambodia, Laos, and Vietnam - Witsanu Saisorn; Jiratthi Satthaphorn; Shuichiro Tagane (Plants, 2025)
A taxonomy of the genus Phyllodium Desv. in Cambodia, Laos, and Vietnam is presented. The plant specimens collected from the fields and herbarium specimens kept at Asian and European herbaria are examined. The IUCN conservation status of each species at regional and national levels is assessed. Five species are enumerated, viz., Phyllodium elegans (Lour.) Desv., P. kurzianum (Kuntze) H.Ohashi, P. longipes (Craib) Schindl., P. pulchellum (L.) Desv., and P. vestitum Benth. Lectotypification of two names, Desmodium longipes Craib and D. tonkinense Schindl., is performed. A key to the species, description, distribution, ecology, phenology, vernacular names, full list of specimens examined, and photographs are provided. The conservation status of five Phyllodium species varies across Cambodia, Laos, Vietnam, and Indochina. Phyllodium elegans and P. pulchellum are consistently Least Concern (LC) in all regions. Phyllodium kurzianum is Data Deficient (DD) in Laos, Near Threatened (NT) in Vietnam, and LC in Indochina. Phyllodium longipes is EN in Cambodia but LC elsewhere. Phyllodium vestitum is NT in Cambodia, Vulnerable (VU) in Laos and Vietnam, and LC in Indochina. The taxonomic information provided in this work will contribute to the advancement of the Flora of Cambodia, Laos, and Vietnam and the conservation status of each species proposed in this paper can be used for future conservation planning.